FILSAFAT MANUSIA DALAM TUTUR MEDANG KEMULAN - Krishna, Ida Bagus Wika; Untara, I Made Gami Sandi (Sanjiwani: Jurnal Filsafat, 2024)
Medang Kemulan's speech is one of the many speeches containing the teachings of Shiva. Judging from the language used and the sloka texts contained in it, it appears that the Medang Kemulan lontar is an old lontar. Tutur Medang Kemulan is often said to be the underlying source for the emergence of wariga teachings, but Tutur Medang Kemulan also teaches about the philosophy of life as a human. The human philosophy referred to in this Tutur Medang Kemulan research is a deep effort made by humans to understand what humans really are. Where did that human come from? Humans What are the elements that make up humans? Why were humans born? What is the purpose of human birth? Where do humans go after death?The method in this research is qualitative with data collection through literature study. The human philosophy referred to in Tutur Medang Kemulan is a deep effort made by humans to understand what humans really are, starting from the aesthetic stage, the ethical stage and continuing to the religious stage. The teachings of human philosophy in Tutur Medang Kemulan also mention the behavior of Sang Watugunung as a) an eccentric being, b) a paradoxical being, c) a multidimensional being, d) a cultural being.